(untitled) (Balneo and PRM Research Journal, 2024)
Introduction: Ledderhose disease (LD), a rare and benign pathology, manifests in the thickening of the plantar aponeurosis, leading to the development of nodules on the plantar surfaces. First stages typically feature painless nodules, but progression may result in discomfort or pain attributed to inflammatory and irritating processes. Also known as plantar fibromatosis (PF), this condition is part of a spectrum of pathologies characterized by hyperproliferation of fibrous connective tissue, similar to Dupuytren contracture (palmar fibromatosis). Given that this pathology is relatively unknown but potentially disabling, we consider it important to review this condition in order to manage possible complications and to expand the rehabilitation treatment, currently limited to a few physiotherapy procedures. Materials and methods: This paper presents the case of a 66-year-old patient known to have Ledderhose disease diagnosed in 2003, Dupuytren contracture of bilateral hands, osteopenia, invasive ductal carcinoma surgically treated and followed by chemotherapy and radiotherapy (2018). The patient presented to our clinic complaining of bilateral plantar pain, with the left side exhibiting greater severity, accompanied by paresthesia in a sock-like distribution and difficulty with ambulation. On clinical examination, bilateral flatfoot deformity, stage 1 Dupuytren contracture of the bilateral palmar aponeurosis, mildly reduced distal muscle strength in both upper and lower extremities and plantar synovial cysts were noted, findings that were subsequently confirmed via MRI imaging. The physiotherapeutic plan was designed to reduce symptomatic manifestations, attenuate the inflammatory cascade and optimize gait pattern. However, considering the patient’s medical history, we were limited in prescribing physiotherapy procedures. The patient was dynamically evaluated using the following scales: Visual analogue scale (VAS), Life Quality Assessment (QOL), The Functional Ambulation Categories (FAC), Index of Independence in Activities of Daily Living (ADL) and Medical Research Council Scale for muscle strength (MRC). Results: Considering the associated oncological pathology, our ability to prescribe physiotherapy procedures was constrained. However, the patient benefited from an individualized rehabilitation program specific to the pathology with a favorable evolution and a promising prognosis. The program included physical therapy sessions targeting stretching, toning and enhancing muscle strength for the plantar and palmar muscle groups, alongside paraffin applications, low-frequency current (Transcutaneous Electrical Nerve Stimulation - TENS) and Deep oscillation applications. Conclusions: The complex rehabilitation approach in a patient with a rare medical condition, complicated with degenerative diseases, though limited in variety due to associated oncological pathology contributed in the end to a significant improvement of the patient’s quality of life.